2020
DOI: 10.1002/pa.2120
|View full text |Cite
|
Sign up to set email alerts
|

Role of blogging in perceived learning and satisfaction of students

Abstract: The contemporary smart concepts of education signify a heavy role of blogging tools in digital learning environments that have a substantial effect on students' learning and satisfaction. This study aims to analyze the influence of students' four perceptions about blogging that is, perception of digital technology (PDT), perceptions of teaching and learning (PTL), perceptions of previous blogging experience (PBE), and perceived usefulness of blogging (PUB) on the frequency of blogging and then assesses the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The authors aim to improve student writing skills through blogging, and it was found in the study that the students are interested in the continual use of blogs even after the academic session (Forrester, Ashman & Kuebbing, 2022). Khan et al (2021) confirmed the students perceived learning and satisfaction through blogging in HEIs as their perception revolves around digital technology, teaching and learning, previous blogging experience and the usefulness of blogging.…”
Section: Introductionmentioning
confidence: 81%
“…The authors aim to improve student writing skills through blogging, and it was found in the study that the students are interested in the continual use of blogs even after the academic session (Forrester, Ashman & Kuebbing, 2022). Khan et al (2021) confirmed the students perceived learning and satisfaction through blogging in HEIs as their perception revolves around digital technology, teaching and learning, previous blogging experience and the usefulness of blogging.…”
Section: Introductionmentioning
confidence: 81%
“…This media is applied to various subjects, especially science and language. It is also supported that the use of blog media can increase learning motivation, improve classroom experience and support instructional classroom activities (Barro et al, 2015), improve student achievement and learning motivation (Çelik et al, 2018), improve learning outcomes (Garcia et al, 2019;Lazarević, T., Miljanović, T., Zarić, G., & Županec, 2018;Ramdiah et al, 2020;Siregar et al, 2020;Suprihatien et al, 2019) writing skills (Alsamadani, 2017;Fithriani et al, 2019;Sa'diyah & Cahyono, 2019) increasing activeness and motivation (Nugroho, 2018), increasing positive attitudes and satisfaction in Learning (Khan et al, 2021) increasing ability critical thinking (Fathani & Baidawi, 2020), and improve understanding the concept (Rostika et al, 2020) as well as increasing self-confidence and understanding of the environment (Kahraman, 2021).…”
Section: Introductionmentioning
confidence: 99%